2010
DOI: 10.1002/lt.22166
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival after 67 hours of anhepatic state due to primary liver allograft nonfunction

Abstract: Primary liver allograft nonfunction immediately after transplantation poses a life-threatening situation for the recipient. Emergency retransplantation may not be immediately possible due to organ unavailability. Total hepatectomy with temporary portacaval shunt has been described as a bridge to retransplantation when the presence of the graft appears to be harming the recipient. Case reports of retransplantation after total hepatectomy with anhepatic times greater than 48 hours routinely describe poor outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
1
11
1
Order By: Relevance
“…Introduced by Ringe et al 57 more than 2 decades ago, its use has been reported under such circumstances, also in nontrauma patients developing hemodynamic instability with the longest anhepatic time of 67 hours. [58][59][60] Notably, a nonsignificant increase in 90-day risk of graft loss after 2-stage transplantations was found in the present study. Although a lack of significance with respect to the risk of graft loss may be related to a low number of patients undergoing 2-stage operations, this is not the case for postoperative mortality, which was identical after 1-and 2-stage operations.…”
Section: Differences In Baseline Characteristics Between Patients Und...contrasting
confidence: 75%
“…Introduced by Ringe et al 57 more than 2 decades ago, its use has been reported under such circumstances, also in nontrauma patients developing hemodynamic instability with the longest anhepatic time of 67 hours. [58][59][60] Notably, a nonsignificant increase in 90-day risk of graft loss after 2-stage transplantations was found in the present study. Although a lack of significance with respect to the risk of graft loss may be related to a low number of patients undergoing 2-stage operations, this is not the case for postoperative mortality, which was identical after 1-and 2-stage operations.…”
Section: Differences In Baseline Characteristics Between Patients Und...contrasting
confidence: 75%
“…Indications for rescue hepatectomy include post‐transplant complications, fulminant native hepatic failure, and liver trauma, among others 17,20–24 . Previous studies have shown that among transplant recipients, anhepatic patients experience high mortality 3–5,11 . The utilization of rescue hepatectomy and anhepatic status in the United States has not been studied and, to our knowledge, this is the first analysis of the national experience of this practice as a bridge to liver retransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The anhepatic patient requires astute anesthetic and critical care management with attention to electrolyte balance, body temperature, coagulopathy, renal function, with the potential for cerebral edema 8–10 . Anhepatic patients can experience high mortality without timely retransplantation, so the intent of rescue hepatectomy and retransplantation as two stages are to stabilize and salvage a patient 11 . An allograft is often not always immediately available placing the patient in a vulnerable position 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Arora and coworkers reported anatomic anhepatic time 67 hours for a patient with primary nonfunction, and this is the longest anhepatic time in the literature. 10 Anhepatic times < 30 hours are well tolerated. 5 There are several problems during the anhepatic period, and patients require maximal intensive care.…”
Section: Discussionmentioning
confidence: 99%